Periodontal Therapy in a Patient Undergoing Orthodontic Treatment: Case Report (REMUNOM, 2025)
The integration of a multidisciplinary treatment between orthodontics and periodontics is essential to ensure the control of dental biofilm, the main etiological agent of inflammatory processes of the dental supporting tissues, such as gingivitis and periodontitis. This study aimed to report a clinical case of a patient with gingivitis who is undergoing orthodontic treatment at the School of Dentistry of the University Center of Patos (UNIFIP). After the diagnosis, an individualized periodontal treatment plan was developed through basic periodontal therapy and surgical complementation. The basic procedures were performed in three clinical sessions. After reevaluation, the patient underwent periodontal surgical therapy, where the external bevel gingivectomy technique was chosen to remove excess gingival tissue. Patients who wear orthodontic appliances should take extra care and visit their dentist regularly to encourage oral health care, reduce plaque buildup and minimize the risk of inflammatory gingival hyperplasia. Gingivectomy is a quick, low-cost procedure that has a favorable prognosis with low chances of recurrence, ensuring an adequate postoperative period with tissue repair.